Acceptability and design preferences of supervised injection services among people who inject drugs in a mid-sized Canadian City - Mitra, Sanjana (Harm Reduct J, 2017)
BACKGROUND: Supervised injection services (SIS) have been shown to reduce the public- and individual-level harms associated with injection drug use. While SIS feasibility research has been conducted in large urban centres, little is known about the acceptability of these services among people who inject drugs (PWID) in mid-sized cities. We assessed the prevalence and correlates of willingness to use SIS as well as design and operational preferences among PWID in London, Canada. METHODS: Between March and April 2016, peer research associates administered a cross-sectional survey to PWID in London. Socio-demographic characteristics, drug-use patterns, and behaviours associated with willingness to use SIS were estimated using bivariable and multivariable logistic regression models. Chi-square tests were used to compare characteristics with expected frequency of SIS use among those willing to use SIS. Design and operational preferences are also described. RESULTS: Of 197 PWID included in this analysis (median age, 39; interquartile range (IQR), 33–50; 38% female), 170 (86%) reported willingness to use SIS. In multivariable analyses, being female (adjusted odds ratio (AOR) 0.29; 95% confidence interval (CI) 0.11–0.75) was negatively associated with willingness to use, while public injecting in the last 6 months (AOR 2.76; 95% CI 1.00–7.62) was positively associated with willingness to use. Participants living in unstable housing, those injecting in public, and those injecting opioids and crystal methamphetamine daily reported higher expected frequency of SIS use (p < 0.05). A majority preferred private cubicles for injecting spaces and daytime operational hours, while just under half preferred PWID involved in service operations. CONCLUSIONS: High levels of willingness to use SIS were found among PWID in this setting, suggesting that these services may play a role in addressing the harms associated with injection drug use. To maximize the uptake of SIS, programme planners and policy makers should consider the effects of gender and views of PWID regarding SIS design and operational preferences.